Changing Mindsets: Organisational Culture as the Primary Barrier to Public Sector Performance Reform (African Journal of Public Administration & Management, 2026)
Changing Mindsets: Organisational Culture as the Primary Barrier to Public Sector Performance Reform Despite widespread adoption of performance management frameworks, African public sectors face challenges in achieving optimal governance that balances procedural requirements with citizen needs. Drawing on Cameron and Quinn's Competing Values Framework and institutional theory, this study explores how organisational culture influences governance effectiveness in Eswatini's Ministry of Public Service. The research employs qualitative methodology with triangulated data collection: focus groups with Heads of Departments (n=10), semi-structured interviews with officers (n=25), and comparative documents analysis across six African countries ( Ghana, Kenya, South Africa, Eswatini, Tanzania and Nigeria). Findings reveal dominant hierarchy culture characterized by top-down control and conformity, and an emphasis on compliance rather than innovation. This creates implementation challenges: departmental silos affecting service coordination, limited strategic planning reducing citizen-outcome connections, and cautious processes emphasizing procedural adherence over innovative solutions. Comparative analysis demonstrates similar patterns across African contexts, suggesting systemic cultural considerations transcending national boundaries. The study recommends mindset transformation strategy encompassing: diagnostic assessment of entrenched hierarchy models, leadership development modeling adaptive thinking, structural interventions replacing silos with collaborative teams, and reinforcement mechanisms shifting from procedural focus to innovation-oriented approaches. Without interventions to fundamentally change mindsets from rule-bound procedures to performance-oriented approaches, reforms will remain ineffective across African contexts.